Acute and overuse elbow trauma: radio-orthopaedics overview - Nocerino, Elisabetta Antonia; Cucchi, Davide; Arrigoni, Paolo; Brioschi, Marco; Fusi, Cristiano; Genovese, Eugenio A.; Messina, Carmelo; Randelli, Pietro; Masciocchi, Carlo; Aliprandi, Alberto (Acta Biomedica Atenei Parmensis, 2018)
The correct management of acute, subacute and overuse-related elbow pathologies represents a challenging diagnostic and therapeutic problem. While major trauma frequently requires a rapid surgical intervention, subluxation and minor trauma allow taking more time for diagnostics and planning the correct elective treatment after careful clinical and radiological investigation. In these conditions, communication between orthopaedic surgeon and radiologist allow to create a detailed radiology report, tailored to the patient’s and surgeon’s needs and optimal to plan proper management. Imaging technique as X-Ray, CT, US, MRI, CTA and MRA all belong to the radiologist’s portfolio in elbow diagnostics. Detailed knowledge of elbow pathology and its classification and of the possibilities and limits of each imaging technique is of crucial importance to reach the correct diagnosis efficiently. The aim of this review is to present the most frequent elbow pathologies and suggest a suitable diagnostic approach for each of them.